1988
DOI: 10.1063/1.100113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermal stress-induced grain boundary cavitation and notching in narrow Al-Si metallizations

Abstract: Grain boundary voiding and notching have been found to produce failures in narrow metallizations during thermal aging. The nucleation and growth of grain boundary voids are considered to occur as a result of grain boundary sliding and the subsequent stress-induced mass transport. A proposed model yields the linewidth and temperature dependence of the observed failure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, OFF-ON is wholly different from the hillock formation for several reasons. Many studies , concerning whiskers (or hillocks) have been conducted in an effort to find methods to prevent hillock formation, which is a detrimental to the reliability of electronic packaging systems. OFF-ON can be exploited to grow perfect single-crystalline Bi nanowires for fundamental transport studies and possibly for use in thermoelectric applications.…”
mentioning
confidence: 99%
“…However, OFF-ON is wholly different from the hillock formation for several reasons. Many studies , concerning whiskers (or hillocks) have been conducted in an effort to find methods to prevent hillock formation, which is a detrimental to the reliability of electronic packaging systems. OFF-ON can be exploited to grow perfect single-crystalline Bi nanowires for fundamental transport studies and possibly for use in thermoelectric applications.…”
mentioning
confidence: 99%
“…Since 1984 it has been observed that voids form in A1 interconnects under a passivation layer, even under zero current density [168][169][170][171][172][173][174][175][176][177][178]. Since there is mechanlcal constraint in unpassivated interconnects, no stress voiding has been reported so far in the unpassivated lines.…”
Section: B2 Stress Induced Voiding In A1 Interconnectsmentioning
confidence: 99%
“…Voids in Al lines have been seen to grow even at room temperatures [4] and the problem of thermal stress voiding is becoming more serious as line widths continue to decrease [5,6] It has been argued that void nucleation occurs, during cooldown from passivation temperatures, due to grain boundary sliding-induced stress concentrations at the intersection between a grain boundary and the passivation [6].…”
Section: Introductionmentioning
confidence: 99%